Carbon quantum dots coupled Au nanoparticle as fluorescence-based DNA biosensors for dengue virus detection - Monday, Yakubu Newman; Jaafar Abdullah; Nor Azah Yusof; Suraya Abdul Rashid; Rafidah Hanim Shueb; Hamidah Sidek (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study introduces a novel DNA biosensor probe comprising carbon quantum dots (CQDs) derived from palm kernel shell biomass and gold nanoparticles (AuNPs) synthesized via the citrate reduction method. The CQDs were doped with ethylenediamine using a hydrothermal process employing a one-pot synthesis method in an autoclave batch reactor. The resulting CQDs exhibited exceptional photoluminescent (PL) properties, with an excitation wavelength of 360 nm and an emission wavelength of 430 nm. Transmission electron microscope (TEM) images showed the average particle sizes of the CQDs and AuNPs to be 2 nm and 15 nm, respectively. Carboxylic acid-modified CQDs were coupled to amine-modified ssDNA (PA) to construct the biosensor through the amine coupling technique. The AuNPs were modified through thiol coupling with Rhodamine B, L-cysteine, and thiol-modified ssDNA (PT). Both PA and PT probes were designed to complement the DEN-3 virus oligonucleotide. CQDs acted as fluorophores and energy donors in the biosensor, while the AuNPs functioned as nanoquenchers of fluorophores and energy acceptors. The resulting probe pair, CQDs-PA, and AuNPs-PT demonstrated remarkable Förster resonance energy transfer (FRET) and exhibited fluorescence turn-on upon titration with DEN-3. The biosensor displayed excellent sensitivity with a logarithmic calibration equation of 5.22LogC + 20.79 (R2 = 0.979), covering a linear range of 0.001 nM to 100 nM. The limit of detection (LOD) was determined to be 1.57 ± 0.71 nM. This innovative DNA biosensor, incorporating CQDs and AuNPs, holds promising potential for sensitive and specific detection of the DEN-3 virus.